2021
DOI: 10.2147/ijn.s327598
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Therapy Using Doxorubicin-Loading and Nitric Oxide-Generating Hollow Prussian Blue Nanoparticles with Photoacoustic Imaging Potential Against Breast Cancer

Abstract: Traditional antitumor chemotherapy faces great challenges, such as multidrug resistance (MDR) and poor penetration into tumor tissues. The newly emerging nitric oxide (NO)-based gas therapy has been recognized to reduce MDR and has improved permeation into tumor tissue. Methods: In this study, NO-generating prodrug sodium nitroprusside (SNP) was doped to hollow mesoporous Prussian blue (PB) nanoparticles to fabricate NO-generating nanoparticles (NO-PB), which was further loaded with doxorubicin (DOX). Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…The understanding of such a mass distribution, density gradient, or connectivity network may have important implications for understanding the tumor biology and for its medical treatment. Notably, both therapy and imaging are often affected by tumor penetration difficulty, either by the drug or by the imaging contrast agent [ 2 ]. As an example, treatment by chemotherapy may be optimal only at the tumor periphery, because the progress of the drug into the tumor center may be hampered by the TME’s acidity.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of such a mass distribution, density gradient, or connectivity network may have important implications for understanding the tumor biology and for its medical treatment. Notably, both therapy and imaging are often affected by tumor penetration difficulty, either by the drug or by the imaging contrast agent [ 2 ]. As an example, treatment by chemotherapy may be optimal only at the tumor periphery, because the progress of the drug into the tumor center may be hampered by the TME’s acidity.…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed NO-based gas treatment has been shown to lower multidrug resistance (MDR) and enhance absorption into tumor tissue. Fu et al have innovatively doped sodium nitroprusside (SNP) into HPB nanoparticles as a precursor, which can produce NO and be used for drug delivery (NO-PB) [ 96 ]. The results demonstrated that the release rate of DOX NO-PB was faster in acidic conditions than in neutral pH conditions.…”
Section: Application Of Enzyme Activity Of Pbnpsmentioning
confidence: 99%
“…Also aiming at breast cancer therapy, Fu et al prepared doxorubicin (DOX)-loaded mesoporous Prussian blue NPs doped with the nitric oxide-producing prodrug sodium nitroprusside (NO-PB). 123 The authors showed that the release of encapsulated DOX was pH-dependent and that the particles produced NO molecules in cells, accumulated in tumor tissue, and could be imaged by PAM.…”
Section: Imaging Techniquesmentioning
confidence: 99%